(untitled) (Global Journal of Human-Social Science, 2019)
The study examined the extent to which the Nigerian youths were able to participate in the 2019 general elections compared to the previous ones from 1999. It also examined the fate of the Nigerian youths with the passage of the Not Too Young to Rule (NTYTR) Act. The study also assessed the effect of the NTYTR Act on the 2019 general elections in Nigeria. The study adopted quantitative method of research with the use of a self-structured questionnaire that was administered on 200 youth respondents between the ages of 18 and 35 years in Osun State. Data were analyzed quantitatively and presented in bar charts, tables and chi square statistics. The study found that the Nigerian youths did not participate fully in previous general elections compared to 2019 after the passage of the NTYTR Act in the country. The study showed that the NTYTR Act made the outcomes of the 2019 general elections to be better than previous elections because youths are now more encouraged to take part in the electoral contest unlike what it used to be.